SISTEM INFORMASI BENGKEL DAN SUKU CADANG BINTANG NUSANTARA MOTOR BERBASIS DESKTOP - , RIDO PRASOJO D P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Workshop and spare parts management of Bintang Nusantara Motor requires an information system that can help process sales transactions services. At first, the system used in Bintang Nusantara Motor still using still manual is wrote on the book. So that data processing is becoming ineffective because they have to write into the book, and then move it into Ms. Excel and make a report. The solution to solve the problems that occur in Bintang Nusantara Motor is making information systems can handle data processing and documenting at workshop and spare parts of Bintang Nusantara Motor. This information systems built used Java programming language and used the MySQL database. This information system is able to process data such as transaction data, product data, motor data, purchasing data, customer data, the data suggestions, employee data and payroll data.. Additionally, the system is able of providing output in the form of a transaction note, evidence taking salaries, and report. Workshop and spare parts report includes transaction reports, purchases report, employee payment, and report income and expense workshop and spare parts reports.